2016
DOI: 10.1186/s12872-016-0337-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of affective temperaments with blood pressure and arterial stiffness in hypertensive patients: a cross-sectional study

Abstract: BackgroundAffective temperaments (anxious, depressive, cyclothymic, irritable and hyperthymic) measure subclinical manifestations of major mood disorders. Furthermore, cumulating evidence suggests their involvement in somatic disorders as well. We aimed to assess associations between affective temperament scores and blood pressure and arterial stiffness parameters in hypertensive patients.MethodsIn this cross-sectional study, 173 patients with well-controlled or grade 1 chronic hypertension, with no history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 50 publications
3
13
0
10
Order By: Relevance
“…BAs 9, 13 and 31, partitions of the frontal lobe and the upper posterior cingulate cortex, are mainly connected with cognitive function as well as emotional processing and recognition. In the study of László et al affective temperaments were associated with the pathogenesis of hypertension, suggesting that patients who presented high cyclothymic temperament were in a higher risk of elevated blood pressure [39]. What is more, before evolving into stroke, there has been an impairment of the brain morphology and cognitive function of patients with hypertension to a certain degree, leading to depression or anxiety in future disease progression [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…BAs 9, 13 and 31, partitions of the frontal lobe and the upper posterior cingulate cortex, are mainly connected with cognitive function as well as emotional processing and recognition. In the study of László et al affective temperaments were associated with the pathogenesis of hypertension, suggesting that patients who presented high cyclothymic temperament were in a higher risk of elevated blood pressure [39]. What is more, before evolving into stroke, there has been an impairment of the brain morphology and cognitive function of patients with hypertension to a certain degree, leading to depression or anxiety in future disease progression [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of depression and CVD show several similarities including metabolic and immunomodulatory dysregulation, autonomic dysfunction, and sympathetic overstimulation ( 37 ) as well as increased arterial stiffness ( 38 ). Arterial stiffness causes an increase in blood pressure, which leads to an additional burden for the vascular system and may, in turn, induce further stiffening of the arteries ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several studies on psychiatric patients have reported that hyperthymic temperament is associated with bipolar disorder and is also a protective factor for suicide . The few papers that have investigated affective temperament in patients with medical conditions did not examine the association between temperament and other psychological features. The protective role of hyperthymic temperament is probably due to a more effective coping strategy; indeed, coping strategy is known to play a crucial role in people's health, with major implications on both subjective and psychological well‐being…”
Section: Discussionmentioning
confidence: 99%